Pengaruh Marketing Affiliate Terhadap Keputusan Pembelian(Studi Kasus pada E-commerce Shopee) - Hening Lintang Kinanthi; Aditya Bayu Kusuma (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Marketing is no longer just referring to traditional advertising and personal promotion. One of the digital marketing techniques that is currently trending is Affiliate Marketing. And Shopee is one of the e-commerce that uses affiliate marketing as one of its marketing activities. The rapid development of e-commerce platforms and social media in the use of Affiliate marketing has encouraged the author to conduct research to examine the factors of Affiliate marketing that can influence Purchasing decisions. For this reason, the title "The Influence of Affiliate Marketing on Purchasing Decisions on Shopee Ecommerce" was raised. The study uses a qualitative approach using literacy studies from research journals, weblinks, and theoretical reference books and also interviews. The results of this study are that the Affiliate marketing variable influences product purchasing decisions in e-commerce. Through this research, it is hoped that it can open deeper insights into the effectiveness of using Affiliate Marketing on purchasing decisions on online platforms.